The role of civics teachers in forming disciplined character in class XI students (case study of Al-Bukhary Vocational School) - Putra, Dian Syah; Toni, Toni; Rohana, Rohana; Saragih, Siti Zahara (Lembaga Riset Mutiara Akbar, 2026)
This study aims to analyze the role of Pancasila and Citizenship Education (PPKn) teachers in shaping the disciplined character of eleventh-grade students at Al-Bukhary Vocational School. The study used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation of teachers and students. The results showed that PPKn teachers have a strategic role as inspirators, motivators, and role models in instilling discipline values through punctuality, compliance with school rules, and providing real-life examples of behavior. Forms of disciplinary violations found included being late to school, not attending ceremonies, truancy, wearing incomplete attributes, and irregular clothing. The main obstacles to developing disciplined character stem from low internal motivation in students, lack of family support, and negative social influences. Efforts made include providing advice, gradual guidance, implementing educational sanctions, and collaboration between teachers, parents, and the school. This study confirms that the formation of disciplined character does not only depend on the role of teachers, but requires synergy between the family, school, and community environments so that disciplined values can be instilled sustainably in students.